Overreaction Effect in the Tunisian Stock Market - Chaouachi, Olfa; Douagi, Fatma Wyème Ben Mrad (Journal of Asian Business Strategy, 2014)
In this paper, we examine the existence of the overreaction effect in the Tunisian stock market over the period January 1999 to December 2013 and we try to explain this phenomenon. Using the methodology of De Bondt and Thaler (1985), we report evidence in favour of the overreaction effect. Securities which have underperformed the market over the past three years will outperform the market over the following three years. Also, we find that the overreaction is not a manifestation of the January effect. The excess returns of the loser portfolios are not realized in January. Furthermore, we document that the difference in performance between the loser and winner portfolios is not attributed to the size effect. However, we find that the overreaction effect in the TSE can be explained by the differences in risk.